2016
DOI: 10.3390/land5040036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Landscape Composition on the Abundance of Laodelphax striatellus Fallén in Fragmented Agricultural Landscapes

Abstract: Abstract:The spatial distribution of crop and non-crop habitats over segmented agricultural landscapes could be used as a means to reduce insect pest populations. Seven land cover categories such as wheat, rapeseed, vegetable, water, built-up, paved road, and unsurfaced road were extracted from GeoEye satellite images dating from late May to late June of 2010. Three diversity metrics and three evenness metrics were estimated from the abovementioned land cover categories for quantifying the effect of landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 41 reported that the abundance of L. striatellus was related to the proportion of orchards in the landscape in the late season. It is known that different crop management techniques in the agroecosystem affect the pattern of vector abundance and vary between years, especially for overwintering adults 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 reported that the abundance of L. striatellus was related to the proportion of orchards in the landscape in the late season. It is known that different crop management techniques in the agroecosystem affect the pattern of vector abundance and vary between years, especially for overwintering adults 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Clemente-Orta et al 41 reported that the abundance of L. striatellus was related to the proportion of orchards in the landscape in the late season. It is known that different crop management techniques in the agroecosystem affect the pattern of vector abundance and vary between years, especially for overwintering adults 48,49 . The non-detection of MRDV in any of the analysed weeds confirms the reduced number of alternative hosts of this virus as well as their reduced susceptibility 14,16,18,20 .…”
Section: Ra (%)mentioning
confidence: 99%